Endothelial Dysfunction, Atherosclerosis, and Increase of von Willebrand Factor and Factor VIII: A Randomized Controlled Trial in Swine - Atiq, Ferdows; van de Wouw, Jens; Sorop, Oana; Heinonen, Ilkka; de Maat, Moniek P. M.; Merkus, Daphne; Duncker, Dirk J.; Leebeek, Frank W. G. (Thrombosis and Haemostasis, 2021)
It is well known that high von Willebrand factor (VWF) and factor VIII (FVIII) levels are associated with an increased risk of cardiovascular disease. It is still debated whether VWF and FVIII are biomarkers of endothelial dysfunction and atherosclerosis or whether they have a direct causative role. Therefore, we aimed to unravel the pathophysiological pathways of increased VWF and FVIII levels associated with cardiovascular risk factors. First, we performed a randomized controlled trial in 34 Göttingen miniswine. Diabetes mellitus (DM) was induced with streptozotocin and hypercholesterolemia (HC) via a high-fat diet in 18 swine (DM + HC), while 16 healthy swine served as controls. After 5 months of follow-up, FVIII activity (FVIII:C) was significantly higher in DM + HC swine (5.85 IU/mL [5.00–6.81]) compared with controls (4.57 [3.76–5.40], p = 0.010), whereas VWF antigen (VWF:Ag) was similar (respectively 0.34 IU/mL [0.28–0.39] vs. 0.34 [0.31–0.38], p = 0.644). DM + HC swine had no endothelial dysfunction or atherosclerosis during this short-term follow-up. Subsequently, we performed a long-term (15 months) longitudinal cohort study in 10 Landrace–Yorkshire swine, in five of which HC and in five combined DM + HC were induced. VWF:Ag was higher at 15 months compared with 9 months in HC (0.37 [0.32–0.42] vs. 0.27 [0.23–0.40], p = 0.042) and DM + HC (0.33 [0.32–0.37] vs. 0.25 [0.24–0.33], p = 0.042). Both long-term groups had endothelial dysfunction compared with controls and atherosclerosis after 15 months. In conclusion, short-term hyperglycemia and dyslipidemia increase FVIII, independent of VWF. Long-term DM and HC increase VWF via endothelial dysfunction and atherosclerosis. Therefore, VWF seems to be a biomarker for advanced cardiovascular disease.
Keywords: von Willebrand factor; von Willebrand disease; diabetes mellitus; endothelial dysfunction; atherosclerosis; cardiovascular disease; swine